Chromosome-scale genomes of Quercus sichourensis and Quercus rex provide insights into the evolution and adaptation of Fagaceae - Liu, Xue; Zhang, Weixiong; Zhang, Yongting; Yang, Jing; Zeng, Peng; Tian, Zunzhe; Sun, Weibang; Cai, Jing (Journal of genetics and genomics, 2024)
The Fagaceae, a plant family with a wide distribution and diverse adaptability, has garnered significant interest as a subject of study in plant speciation and adaptation. Meanwhile, certain Fagaceae species are regarded as highly valuable wood resources due to the exceptional quality of their wood. In this study, we present two high-quality, chromosome-scale genome sequences for Quercus sichourensis (848.75 Mb) and Quercus rex (883.46 Mb). Comparative genomics analysis reveals that the difference in the number of plant disease resistance genes and the nonsynonymous and synonymous substitution ratio (Ka/Ks) of protein-coding genes among Fagaceae species are related to different environmental adaptations. Interestingly, most genes related to starch synthesis in the investigated Quercoideae species are located on a single chromosome, as compared to the outgroup species, Fagus sylvatica. Furthermore, resequencing and population analysis of Q. sichourensis and Q. rex reveal that Q. sichourensis has lower genetic diversity and higher deleterious mutations compared to Q. rex. The high-quality, chromosome-level genomes and the population genomic analysis of the critically endangered Q. sichourensis and Q. rex will provide an invaluable resource as well as insights for future study in these two species, even the genus Quercus, to facilitate their conservation.